Associations of temperature and precipitation with malaria in children under 5: A multi-country study in Sub-Saharan Africa - Suleiman Chombo; Jovine Bachwenkizi; Huda Omary; Heavenlight A. Paulo; Pankras Luoga; Abdallah Zacharia; Jackline Vicent Mbishi; John D. Andrew; Isaac Y. Addo (PLoS ONE, 2025)
Climate change is a significant global challenge with major impacts on human health. It directly affects vector-borne diseases such as malaria by expanding vector ranges, boosting reproduction and biting rates, and shortening pathogen incubation periods. This study aimed to evaluate the association of temperature and precipitation with malaria transmission among children under five in Sub-Saharan Africa (SSA). We employed an analytical cross-sectional design to examine the relationship between temperature, precipitation, and malaria transmission among 15,009 children aged under five in six SSA countries: Burundi, Burkina Faso, Malawi, Nigeria, Tanzania, and Uganda. Historical climate data (temperature and precipitation) were retrieved from ERA-5 for the 12 months preceding the surveys. Weighted Modified Poisson regression model was used to assess the associations between climatic variables and malaria transmission. Malaria prevalence in the sample averaged 25.9%, with Nigeria (38.1%) and Burundi (38.0%) showing the highest rates. The results indicate that a one-degree Celsius rise in temperature increased malaria risk by 1.77-fold (95% CI: 1.297–2.414, p < 0.001), while a one-unit rise in squared temperature reduced risk by 1% (95% CI: 0.984–0.997, p = 0.002). Children living in regions with annual precipitation between 250–500 mm faced a 72% higher risk of malaria than those in areas receiving over 500 mm (95% CI: 1.331–2.212, p < 0.001), highlighting the nonlinear influence of climate on malaria transmission among vulnerable populations. In conclusion, the findings suggest a significant link between precipitation, temperature and increased malaria transmission in SSA. This underscores the importance of incorporating climate data into malaria control strategies to mitigate transmission risks among vulnerable populations.